The Effectiveness of Demonstration Methods and Booklets on The Growth and Development Stimulation Skills of Toddlers - Ike Putri Setyatama; Alfina Damayanti (Midwifery and Nursing Research, 2023)
In achieving the SDG's 2030 target, the government is making early detection efforts for children from pregnancy to the age of 5 years with the aim of increasing survival. The Indonesian government is making efforts to find out the growth and development of children with the SDIDTK program (stimulation of detection and intervention and growth and development). This research is a quantitative research with Two Group Pretest-Posttest Without Control Design. The technique of taking respondents using non-probability sampling. Samples taken in group 1 were 60 people and group 2 were 60 people, so that the total sample was 120 people, who met the inclusion and exclusion criteria. The results of this study indicate that there are significant changes in mothers in stimulating the growth and development of their children before and after being given demonstrations and booklets about stimulation of growth and development. The results of the t-test were 1,962 and the p-value was 0.057 (p-value > 0.05), which meant that there was no difference between growth and development stimulation skills after health education was carried out using the demonstration method or using booklet media. There needs to be involvement or active participation between health workers, mothers, toddlers and their families to cultivate a culture of stimulating growth and development in children, as well as increasing supporting facilities and infrastructure for good growth and development in health service facilities such as health centers and posyandu which are easily accessible by the community.